2022
DOI: 10.3389/fbioe.2022.1021218
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable membrane of poly(l-lactide acid-dioxanone-glycolide) and stereocomplex poly(lactide) with enhanced crystallization and biocompatibility

Abstract: The membranes of poly(l-lactide acid-p-dioxanone-glycolide) (PLPG) with stereocomplex poly(lactic acid) (sc-PLA) were prepared by the solution blending way. It was observed that sc-PLA significantly heightened the crystallizing behavior of PLLA segments of the PLPG matrix. The crystallizing behavior displayed that the temperature of crystallization shifted to a higher range than that of PLPG. Moreover, the half-time of crystallization sharply decreased in value as the sc-PLA content increased in value on accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For fiber reinforced semicrystalline polymer composites, TC structure at the interface is a significant physical interaction 42,43 . The raw CF is lack of nucleation points and difficult to induce TC formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For fiber reinforced semicrystalline polymer composites, TC structure at the interface is a significant physical interaction 42,43 . The raw CF is lack of nucleation points and difficult to induce TC formation.…”
Section: Resultsmentioning
confidence: 99%
“…For fiber reinforced semicrystalline polymer composites, TC structure at the interface is a significant physical interaction. 42,43 The raw CF is lack of nucleation points and difficult to induce TC formation. The PEI-CNT coating layer brought plenty of nucleation sites to strengthen the crystalline ability of CF.…”
Section: Tc Observation and Dsc Measurement Of Pp/cf Micro-compositesmentioning
confidence: 99%
“…It has been reported that 3D ECM gels can promote the growth of stem cells 24 . HA based hydrogels attracted much interest for applications in drug delivery, wound healing and tissue engineering due to their outstanding biocompatibility and biodegradability 25–27 . The oxidation of HA generates aldehyde‐containing HA (A‐HA) whose aldehyde groups can react with amino groups to form hydrogels by Schiff base reaction 28 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Among these systems, there has been considerable interest in the use of polymeric micelles delivery systems composed of biocompatible, biodegradable amphiphilic diblock copolymers. [6][7][8][9] These copolymers are composed of a hydrophobic block, such as poly(lactic acid), poly(lactic-coglycolic acid) and poly(caprolactone), and a hydrophilic block which is typically poly(ethylene glycol) (PEG). [10][11][12] These amphiphilic block copolymers are able to self-assemble in aqueous media to form micelles with a core-shell structure, which are composed of a hydrophobic core surrounded by a highly water bond hydrophilic PEG corona.…”
Section: Introductionmentioning
confidence: 99%
“…A search for improving the solubility of hydrophobic drugs has led to the application of many drug delivery systems such as parenteral emulsion, liposomes, nanoparticles, polymeric micelles, and conjugates 4,5 . Among these systems, there has been considerable interest in the use of polymeric micelles delivery systems composed of biocompatible, biodegradable amphiphilic diblock copolymers 6–9 . These copolymers are composed of a hydrophobic block, such as poly(lactic acid), poly(lactic‐co‐glycolic acid) and poly(caprolactone), and a hydrophilic block which is typically poly(ethylene glycol) (PEG) 10–12 .…”
Section: Introductionmentioning
confidence: 99%